Bolateral Partnering In TM's Global Multimedia Network Services: An Analysis Of Customer Support - Manzlan, Johal (2000)
Partners selection plays an important role to determine cost and support effectiveness. Selecting strategic partners was always an issue in the global business decision making. By establishing bilateral program each partners can leverage their expertise skill and network requirements.